Giardiasis among Under Five Children Living in Tea Plantation Colony at Sylhet District of Bangladesh - Islam, Md Nahidul; Haque, Md Moynul; Aftab, Sharmina; Hoque, Md Anwarul; Das, Premananda; Parvez, Masum; Momtaz, Tahani; Aktar, Jhuma (Bangladesh Journal of Infectious Diseases, 2023)
Background: Giardia lamblia infection is still frequently encountered especially in children living in crowded and unhygienic conditions leading to various public health problems. Objective: The purpose of the study was to detect giardiasis among under five children living in tea plantation colony. Methodology: This cross-sectional observational study was conducted in the Department of Microbiology, Sylhet MAG Osmani Medical College, Sylhet during the period from January 2019 to December 2019. For this purpose children were selected according to inclusion and exclusion criteria irrespective of sex. Four tea garden from Sylhet district namely Malnicherra, Lackatoorah, Tarapur and Burjan were selected randomly for sample collection. Stool samples were collected in sterile, disposable, plastic containers with proper labeling without any preservatives. Cyst of Giardia was determined in stool through microscopic examination. Giardia antigen in stool was detected using ELISA kits. Results: Out of 120 cases, Giardia cyst was found positive in 18(15.0%) cases by microscopy. Giardia antigen was found positive in 23(19.17%) cases by ELISA. ELISA showed sensitivity of 94.13% and specificity of 95.0% when compared with microscopy. Giardia infection was highest in male children (20.0%) than female children. The infection rate was higher (24%) among age group of 36 to 59 months. Conclusion: Giardiasis constitutes a major concern in symptomatic children as well as in asymptomatic children because it causes various public health problem. Bangladesh Journal of Infectious Diseases, December 2022;9(2):53-58